Refractive errors in Filipino eyes in a single-center study population - Karen B. Reyes, MD; Harvey S. Uy, MD (Philippine Journal of Ophthalmology)
Objective: We determined the frequency of refractive errors among Filipino patients undergoing refractive or cataract screening at an ambulatory eye-care center, correlated them with demographic and ophthalmic variables, and compared refractive and keratometric astigmatism.